Revision of the freshwater crabs of the Johora tahanensis (Bott, 1966) species group (Crustacea, Brachyura, Potamidae), with a key to the genus - Peter K. L. Ng (ZooKeys, 2020)
The taxonomy of the potamid freshwater crabs of the Johora tahanensis (Bott, 1966) species group (Potamoidea) is revised. Seven species are recognised, all from Peninsular Malaysia and southern Thailand, three of which are described as new. The three new species were previously identified as J. tahanensis but can be distinguished by characters of the carapace, male first gonopod, and vulva. A revised key to the 18 recognised species of Johora Bott, 1966, is provided.